2016
DOI: 10.3846/16111699.2015.1065905
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Factors for Improving the Iso 14001 Environmental Management System

Abstract: The practice of using environmental management systems (EMS) ISO 14001 at the organisational level indicates that the efficacy of such solutions depends on many factors, both endogenous and exogenous in nature. This article aims to identify the fac- tors that determine the opportunities for the improvement of EMS in organisations, the analysis of the relationship between the factors and the classification of the factors due to their role in the system improvement. The structural analysis was used to classify a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 47 publications
0
18
0
2
Order By: Relevance
“…The most frequently observed percentage was 37.17% for inaccurate evaluations, then negative overall evaluation with a percentage of 31.47%, and hence positive evaluation with a percentage of 31.36% as shown in Figure 1. The negative, inaccurate, and positive percentages for the three dimensions were estimated as 30…”
Section: The Overall Iso 14031 Guidelines Implementation Levels In Samentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently observed percentage was 37.17% for inaccurate evaluations, then negative overall evaluation with a percentage of 31.47%, and hence positive evaluation with a percentage of 31.36% as shown in Figure 1. The negative, inaccurate, and positive percentages for the three dimensions were estimated as 30…”
Section: The Overall Iso 14031 Guidelines Implementation Levels In Samentioning
confidence: 99%
“…Ejdys and Matuszak-Flejszman [29] confirmed that one of the ways of realizing sustainable development principles at the level of an organizational unit is implementation of normalized systems elaborated by ISO. Based on the findings of Ejdys, et al [30], guidelines can be offered to both scholars and practitioners regarding the factors crucial for the improvement of the EMS. Aiming to add value to the existing literature, the structural analysis was adapted to classification and identification of the key factors.…”
Section: Introductionmentioning
confidence: 99%
“…The distinctive feature of RRI approach consists in the aspiration to take stakeholders' needs, concerns and values before a product, service or technology enters the market; to go beyond "not doing wrong" (for example by introducing environmental management systems [48]) towards "doing good". Thus, anticipation, in addition to regulation, becomes a new critical element of innovation governance [49].…”
Section: Discussionmentioning
confidence: 99%
“…The distinctive feature of RRI approach consists in the aspiration to take stakeholders' needs, concerns and values before a product, service or technology enters the market; to go beyond "not doing wrong" (for example by introducing environmental management systems [36]) towards "doing good". Thus, anticipation, in addition to regulation, becomes a new critical element of innovation governance [37].Even more than before, innovators are encouraged to practice reflexivity in the form of foresight [38], Future-Oriented Technology Analysis [39] or innovative forms of Technology Assessment [40,41].…”
Section: Discussionmentioning
confidence: 99%